ANÁLISIS Y DETERMINACIÓN DE LOS ÍNDICES DE SATISFACCIÓN LABORAL DEL TALENTO HUMANO DE LA FISCALÍA PROVINCIAL DE LOJA - Pineda Ayala, Mario Gioseff (2019)
The thesis project has the topic ANALYSIS AND DETERMINATION OF THE LABOR SATISFACTION INDICES OF THE HUMAN TALENT IN THE PROVINCIAL FISCALÍA DE LOJA, it has as main objective to analyze the vulnerable factors of the job satisfaction of the entity's personnel and propose improvement plan to provide solutions to the shortcomings of human talent management. Therefore, used a descriptive research design with the method of measuring job satisfaction called “sum of work facets”, the methods used: deductive, inductive, analytical and descriptive in the development of the research. The techniques of research used: interview directed for the institution's authorities, after that a survey consisting of a 31-item questionnaire, using the Likert scale method were to evaluated to the 115 public employed. In order to gather the necessary information to obtain the necessary results and be the basis for the improvement plan proposed in this research work. The objectives of the thesis were fulfilled: an analysis and determination of the indices of job satisfaction, an institutional diagnosis with: mission, vision, values, strategic objectives, processes, and others.Thedegrees of job satisfaction weredetermined by indices, factors, the results obtained from the applied research techniques were interpreted, and an improvement plan was proposed to boost satisfaction in the most vulnerable factors. With all this, the result obtained was of 2.49 points, equivalent to the degree of very satisfactory within the scale of interpretation used